2001
DOI: 10.1103/physreve.63.051913
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized critical random Boolean networks

Abstract: Standard Random Boolean Networks display an order-disorder phase transition. We add to the standard Random Boolean Networks a disconnection rule which couples the control and order parameters. By this way, the system is driven to the critical line transition. Under the influence of perturbations the system point out self-organized critical behavior. Several numerical simulations have been done and compared with a proposed analytical treatment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…Note that this genuine adaptive network effect can be observed in networks where topological evolution and dynamics of the states take place on separate time scales, as shown in the example presented by Bornholdt & Rohlf. These results inspired several subsequent investigations that extended the results (Bornholdt & Sneppen 1998Luque et al 2001;Kamp & Bornholdt 2002;Bornholdt & Röhl 2003;Liu & Bassler 2006;Rohlf 2007).…”
Section: K3supporting
confidence: 65%
“…Note that this genuine adaptive network effect can be observed in networks where topological evolution and dynamics of the states take place on separate time scales, as shown in the example presented by Bornholdt & Rohlf. These results inspired several subsequent investigations that extended the results (Bornholdt & Sneppen 1998Luque et al 2001;Kamp & Bornholdt 2002;Bornholdt & Röhl 2003;Liu & Bassler 2006;Rohlf 2007).…”
Section: K3supporting
confidence: 65%
“…Boolean networks [1,2,3,4,5,6,7,8] have been extensively studied over the past three decades. They have applications as models of gene regulatory networks, and also as models of social and economic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The mutations affect the connections and the update functions of the nodes. Compared to the simulations in [8,9,10,11,12,13,14,15,16], fitness can be changed by more types of mutations in our model. We let the networks evolve freely under a biologically motivated fitness criterion without imposing any "target properties" to find network topologies that are evolutionary robust.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies of the model [13] showed that the evolved networks are highly canalized. Other models that evolve to a critical state are studied in [14,15,16].…”
Section: Introductionmentioning
confidence: 99%